Correlation between mechanical properties and microscopic structures of an optimized silica fraction in silicone rubber. (8th September 2018) - Liu, Dong; Song, Lixian; Song, Hongtao; Chen, Jie; Tian, Qiang; Chen, Liang; Sun, Liangwei; Lu, Ai; Huang, Chaoqiang; Sun, Guangai
Abstract: The mechanical properties and the hierarchical filler structures were characterized on a series silica-filled silicone rubber with a filler fraction ( Φ Si ) varied from 0.05 phr to 80 phr (parts per hundred rubber). Uniaxial elongation measurement suggests that there is a percolation threshold between 10 and 30 phr. Moreover, an optimum Φ Si range from 40 phr to 50 phr is found, in which the best mechanical performances of reinforcement are shown. The microscopic structures were crosschecked by small-angle neutron scattering (SANS) and scanning electron microscopy (SEM). The effects of the Φ Si and the fabrication process on the morphology of samples are unveiled. The correlation length among aggregates extracted from SANS data monotonically decrease from 237.0 nm to 136.5 nm with increasing the Φ Si from 30 phr to 80 phr. The average radius of gyration of aggregates 〈 R g, agg 〉 fitted with the Beaucage model monotonically decrease from 49.2 nm to 37.5 nm with increasing Φ Si from 10 phr to 80 phr. Providing a 10 nm thickness bound rubber as bridge, samples with optimum Φ Si yield a morphology that the radii of aggregates and the gap filled with polymer matrix in between are equivalent as both around 60 nm.